1974
DOI: 10.1139/f74-143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prey Abundance on Density and Territorial Behavior of Young Rainbow Trout (Salmo gairdneri) in Laboratory Stream Channels

Abstract: When rainbow trout (Salmo gairdneri) fry (underyearlings) were introduced into laboratory channels at three different prey levels and permitted to emigrate voluntarily, their density remained highest at the highest prey level. The distribution of fry was positively associated with a gradient in prey abundance. Both territory size and frequency of aggressive encounter varied inversely with prey level; the higher the prey level, the smaller the territory and the lower the frequency of aggressive encounter. Emigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
87
1
3

Year Published

1980
1980
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(95 citation statements)
references
References 14 publications
4
87
1
3
Order By: Relevance
“…They may also have an indirect lethal effect by causing small brook trout to change habitats. Because survival in young stream salmonids is generally density-dependent (Hunt 1965, LeCren 1972 and the actual density that can survive in a particular place is related to habitat characteristics (Kalleberg 1958, Mason and Chapman 1965, Slaney and Northcote 1974, Mortensen 1977, Dill et al 1981, a change in habitat use may result in a reduction in the number of small brook trout that can survive. These last two potential effects of large rainbow trout on small brook trout may be the result of small brook trout perceiving large rainbow trout either as predators or as superior competitors.…”
Section: Species Introductionmentioning
confidence: 99%
“…They may also have an indirect lethal effect by causing small brook trout to change habitats. Because survival in young stream salmonids is generally density-dependent (Hunt 1965, LeCren 1972 and the actual density that can survive in a particular place is related to habitat characteristics (Kalleberg 1958, Mason and Chapman 1965, Slaney and Northcote 1974, Mortensen 1977, Dill et al 1981, a change in habitat use may result in a reduction in the number of small brook trout that can survive. These last two potential effects of large rainbow trout on small brook trout may be the result of small brook trout perceiving large rainbow trout either as predators or as superior competitors.…”
Section: Species Introductionmentioning
confidence: 99%
“…Foraging sites with negative NEI values were set to zero by default. effect observed in experimental studies (Slaney and Northcote 1974;Keeley 2001;Imre et al 2004). Interestingly, studies incorporating invertebrate drift abundance into estimates of NEI have found positive correlations between salmonid abundance and energy intake rates (Jenkins and Keeley 2010;Urabe et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, research on a presumed optimal size of salmonid territory which would be linked to the quantity of food available proved inconclusive (Slaney and Northcote, 1974;Symons, 1971), except when Dill et al (1981), studying the coho salmon, found a significant inverse relation between territorial size and the quantity of benthic food inside the territory. Yet they were unable to identify the same relation when food was floating above the territories of the subjects.…”
Section: Discussionmentioning
confidence: 99%